A Gamified Recommendation Framework - Amine Talhaoui, Mohamed; Daif, Abderrahmane; Azzouazi, Mohamed; Oubrahim, Younes (International Journal of Engineering and Technology, 2019)
A recommendation system is intended to provide a user with relevant resources based on their preferences. The latter thus reduces his search time but also receives suggestions from the system to which he would not have spontaneously lent attention. The development of the big data technologies and its popularity have included the creation of such systems. Content-based recommendation systems rely on user-based ratings on a set of documents or items. The objective is then to understand the motivations leading him to judge as relevant or not a given item. The gamification aims to use the game to push consumers to do things they would not have done on their own: Fill out a questionnaire, buy a product, watch advertisements or assimilate information. In this paper we join the fields of gamification and recommendation systems to provide a new method and architecture to recommendation.Â Â